2014
DOI: 10.1186/1472-6882-14-433
|View full text |Cite
|
Sign up to set email alerts
|

Research on the efficacy of Celastrus Orbiculatus in suppressing TGF-β1-induced epithelial-mesenchymal transition by inhibiting HSP27 and TNF-α-induced NF-κB/Snail signaling pathway in human gastric adenocarcinoma

Abstract: BackgroundCelastrus orbiculatus has been used as a folk medicine in China for the treatment of many diseases. In the laboratory, the ethyl acetate extract of Celastrus orbiculatus (COE) displays a wide range of anticancer functions. However, the inhibition of the metastasis mechanism of COE in gastric cancer cells has not been investigated so far.MethodsThe present study was undertaken to determine if the anti-metastasis effect of COE was involved in inhibiting of epithelial–mesenchymal transition (EMT) of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…When gastric cancer cells receive signals from their microenvironment, such as TGF-β1, EMT occur and provide cells a distinct advantage in tumor progression and metastasis (48). The present study manifested that TGF-β1 could induce EMT in SGC-7901 cells by downregulating epithelial marker E-cadherin expression and upregulating mesenchymal marker N-cadherin and vimentin expression, consistent with previous reports (49)(50)(51). TSN treatment reversed the above effects of TGF-β1.…”
Section: Discussionsupporting
confidence: 91%
“…When gastric cancer cells receive signals from their microenvironment, such as TGF-β1, EMT occur and provide cells a distinct advantage in tumor progression and metastasis (48). The present study manifested that TGF-β1 could induce EMT in SGC-7901 cells by downregulating epithelial marker E-cadherin expression and upregulating mesenchymal marker N-cadherin and vimentin expression, consistent with previous reports (49)(50)(51). TSN treatment reversed the above effects of TGF-β1.…”
Section: Discussionsupporting
confidence: 91%
“…First indications about a link between HSP27 and cancer stemness appeared in 2010: The small chaperone was shown to be involved in TGF-β1-induced EMT in lung cancer cells (A549 cell line) and this involvement was independent of Smad [138]. Then, the contribution of HSP27 to EMT was found in several different cancer-related studies and models, including breast cancer [139], gastric cancer [140,141], prostate cancer [142,143], renal cell carcinoma [144], and salivary adenoid cystic carcinoma [145]. These HSP27-associated mechanisms of EMT were similar in some cases of cancer while different in others.…”
Section: Hsp27mentioning
confidence: 99%
“…5C). As one of the upstream proteins of snail, NF-κB was examined because early studies indicated that activated NF-κB may accumulate in the nucleolus and serve as an enhancer of snail transcription [33][34][35]. Thus, we hypothesized that radixin knockdown may either reduce the total amount of NF-κB or induce its nuclear exclusion, in turn leading to the repression of snail and the consequent enhancement of E-cadherin transcription.…”
Section: Stable Knockdown Of Radixin Increased the Expression Of E-camentioning
confidence: 99%